Methyl substituent effect on one-dimensional copper(II) coordination polymers containing biologically active ligands: Synthesis, characterization, DNA interactions and cytotoxicities - Senel, Pelin; Inci, Duygu; Aydin, Rahmiye; Huriyet, Huzeyfe; Zorlu, Yunus; Cinkilic, Nilufer (Wiley, 2019)
Three novel water-soluble copper(II) complexes - {[Cu(phen)(trp)]ClO4 center dot 3H(2)O}(n) (1), {[Cu(4-mphen)(trp)]ClO4 center dot 3H(2)O}(n) (2) and [[Cu(dmphen)(trp)(MeOH)][Cu(dmphen)(trp)(NO3)]]NO3 (3) (phen: 1,10-phenanthroline; 4-mphen: 4-methyl-1,10-phenanthroline; dmphen: 4,7-dimethyl-1,10-phenanthroline; trp: l-tryptophan) - have been synthesized and characterized using various techniques. Complexes 1 and 2 are isostructural, and exist as one-dimensional coordination polymers. Complex 3 consists of two discrete copper(II) complexes containing [Cu(trp)(dmphen)(MeOH)](+), [Cu(trp)(dmphen)(NO3)] and one nitrate anion. The binding interaction of the complexes with calf thymus DNA (CT-DNA) was investigated using thermal denaturation, electronic absorption and emission spectroscopic methods, revealing that the complexes could interact with CT-DNA via a moderate intercalation mode. The binding activity of the complexes to CT-DNA follows the order: 3 > 2 > 1. The pUC19 DNA cleavage activity of the complexes was investigated in the absence and presence of external agents using the agarose gel electrophoresis method. Especially, in the presence of H2O2 as an activator, the pUC19 DNA cleavage abilities of the complexes are clearly enhanced at low concentration. Addition of hydroxyl radical scavenger dimethylsulfoxide shows a marked inhibition of the pUC19 DNA cleavage activity of the complexes. In vitro cytotoxic effect of the complexes was examined on human tumor cell lines (Caco-2, A549 and MCF-7) and healthy cells (BEAS-2B). The potent cytotoxic effect of complex 3, with IC50 values of 1.04, 1.16 and 1.72 mu M, respectively, is greater relative to clinically used cisplatin (IC50 = 22.70, 31.1 and 22.2 mu M) against the Caco-2, A549 and MCF-7 cell lines.
Keywords: 10-phenanthroline and derivatives; copper(II) complexes; DNA interactions and cytotoxicity; tryptophan